Uso da centrifuga para determinação da retenção de água para substratos à base de casca de arroz - Diaz, Bárbara da Cunha (2010)
The performance of a substrate is closely related to their physical and chemical properties, and the prior knowledge and study of these characteristics, permit evaluation of its quality and adjust to different use conditions. The agricultural problem in the production of plants in containers is to ensure optimal conditions for biomass production with a development of roots restricted to a small volume of substrate. Physical characterization aims to study the distribution volume of solid material, water and air, which is crucial for plant development. Currently the methodology applied in determining the physical properties of substrates is the same used for soil, presenting some limitations due to some peculiar attributes of the materials used as substrates. The objectives of this study were to develop a methodology for using the centrifuge for determining the water retention in substrates and compare two methods for determining the water retention curve applied to substrates, the tension table method combined with the Richards pressure chamber with the method of centrifuge. The study was conducted at Embrapa Temperate Climate in two steps. The first stage of the study was conducted to determine the centrifugation time necessary to extract all the water available to a given tension. In the second step the two methods were compared using the volume of water retained at different tensions. The study worked on five different substrates: 100% carbonized rice husks; 75% carbonized rice husks + 25% burnt rice husks, 50% carbonized rice husks + 50% burnt rice husks, 25% carbonized rice husks +75% burnt rice husks and 100% burnt rice husk, and three different tensions, 1KPa, 5 KPa and 10 KPa. As a result of the first step the time of two hours of centrifugation was adopted, period considered sufficient for obtaining the equilibrium of retained water in the sample at different tensions. The results showed that the determination of water retention curve of substrates through the centrifuge method, is a potentially viable alternative to the method of the tension table and pressure chamber Richards.